2018
DOI: 10.1177/1532673x18788043
|View full text |Cite
|
Sign up to set email alerts
|

Why Women Win: Gender and Success in State Supreme Court Elections

Abstract: Although women remain underrepresented in U.S. elective office, female candidates have experienced similar or greater electoral success compared to their male counterparts. Research suggests both selection effects (the uniquely strong characteristics and qualifications of women who run for office) and selective candidacy (the decisions to run or not run for office based on the electoral context) contribute to this phenomenon. I leverage a large data set of candidate characteristics and electoral outcomes in st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Thomsen and Sanders (2020) find similar results among state legislators. A recent study of judicial elections found that female lawyers who wish to become state supreme court justices are risk averse and underestimate their abilities; female prospective candidates wait until a seat is open before pursuing an office and delay running until they are certain they will have the “best” qualifications (Nguyen, 2019; but see Williams, 2008). This literature suggests that female judges may be inclined to underestimate their abilities and believe they must overprepare in achievement‐related tasks like writing majority opinions.…”
Section: Experiences In Legal Education and The Path To The Benchmentioning
confidence: 99%
“…Thomsen and Sanders (2020) find similar results among state legislators. A recent study of judicial elections found that female lawyers who wish to become state supreme court justices are risk averse and underestimate their abilities; female prospective candidates wait until a seat is open before pursuing an office and delay running until they are certain they will have the “best” qualifications (Nguyen, 2019; but see Williams, 2008). This literature suggests that female judges may be inclined to underestimate their abilities and believe they must overprepare in achievement‐related tasks like writing majority opinions.…”
Section: Experiences In Legal Education and The Path To The Benchmentioning
confidence: 99%